Pengaruh Kurikulum Merdeka Pada Pembelajaran Ppkn Sebagai Optimalisasi Pembentukan Karakter Siswa Sekolah Dasar - Nazilah Rikhmatus Silmi; Hery Setiyawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Education is an important activity for every person to be able to develop the potential that exists within him. Currently, the curriculum applied to education in Indonesia uses the Merdeka Belajar curriculum. The Merdeka Belajar curriculum has a system where teachers and students can of course have the freedom to learn independently, be creative and innovate. In the Merdeka Belajar curriculum, of course, there are subjects studied by students, one of these subjects is PPKn. The aim of this research is to determine the optimization of the character of elementary school students in PPKn learning based on the Merdeka Belajar curriculum. The type of research used is quantitative, the data collection procedure begins with determining the sample using test techniques, questionnaires, observation rubrics, documentation, as well as the research population and sample, namely class IV students at SDN Balas Klumprik 1 Surabaya. The results of the research show that the Merdeka Belajar curriculum in PPKn learning has an influence in optimizing the character formation of elementary school students. In the conclusion of the research, the influence of the Merdeka Belajar curriculum on PPKn learning as optimizing student character formation in elementary schools is that students are able to optimize character formation in PPKn subjects based on the Strengthening Pancasila Student Profile Project (P5) with the dimension of working together and doing it in life. real.